Prevalence of anaemia in older persons: systematic review. - Gaskell, H; Derry, S; Andrew Moore, R; McQuay, H (2008)
BACKGROUND: Ageing populations will impact on healthcare provision, especially since extra years are not necessarily spent in good health. It is important to identify and understand the significance of common medical problems in older people. Anaemia may be one such problem. We report on the prevalence of anaemia in cohorts of elderly people in the general population. The presence of anaemia is associated with a worse prognosis for both morbidity and mortality. METHODS: Electronic searching and reference lists of published reports were used to identify studies that reported on prevalence of anaemia in cohorts of at least 100 individuals predominantly aged 65 years and over living in developed countries, together with criteria used to define anaemia. Studies of anaemia prevalence in specific disease groups or published before 1980 were excluded. Prevalence data for the entire cohort, for men and women separately and for different age bands were extracted. RESULTS: Forty-five studies contributed data. Thirty-four studies (n = 85,409) used WHO criteria to define anaemia. The weighted mean prevalence was 17% (3-50%) overall, and 12% (3-25%) in studies based in the community (27, n = 69,975), 47% (31-50%) in nursing homes (3, n = 1481), and 40% (40-72%) in hospital admissions (4, n = 13,953). Anaemia prevalence increased with age, was slightly higher in men than women, and was higher in black people than white. Most individuals classified as anaemic using WHO criteria were only mildly anaemic. CONCLUSION: Anaemia, as defined by WHO criteria, is common in older people living in the community and particularly common in nursing home residents and hospital admissions. Predicted demographic changes underline the need to understand more about anaemia in older people.